Mechanical properties of concrete incorporating porcelain granite tiles as partial aggregate - Christine, Wong (2016)
Natural aggregate comprises about 75 % of the components of concrete by volume. The consumption of natural aggregate is high in producing concrete. Thus, making aggregate resources available for our country’s increasing needs will be an ongoing challenge. On the other hand, construction and demolition waste disposed at landfill also increases due to urbanization. The objective of this research is to evaluate the effect of the incorporation of crushed porcelain granite tiles as partial replacement of both coarse and fine aggregate on the mechanical properties of concrete. Six different concrete mixes of C40 grade were cast to test these hardened properties: a conventional reference concrete and five concrete mixes with combination replacement ratios of 10 %, 20 %, 30 %, 40 % and 50 % of natural fine aggregates and 10 % natural coarse aggregate by crushed porcelain granite tiles. In this research, the maximum compressive strength is 65.15 MPa at the combination replacement ratio of 10 % for both coarse and fine aggregate compared to conventional reference concrete, which is 63.11 MPa. The strength increases by 3.23 %. Meanwhile, the maximum flexural strength is 8.47 MPa at the combination replacement ratio of 30% for fine aggregate and 10 % for coarse aggregate, which is 15.07 % of its compressive strength. Nowadays, environmental awareness among the public is affecting the production of natural aggregate. Hence, replacement of natural aggregates with construction and demolition waste materials such as crushed porcelain granite tiles will help in reducing the rate of environmental exploitation, environmental pollution and also landfill waste.